Fully Printed pH Sensor based on Polyaniline/Graphite Nanocomposites. Issue 2 (1st February 2023) - Mahinnezhad, Shirin; Izquierdo, Ricardo; Shih, Andy
Abstract : Recently, there is an exceptional growth in research related to the development of flexible sensors for health analysis. pH measurements can be done non-invasively and continuously, making it an excellent parameter for monitoring different stages of wound healing. Here, we report pH functionality of a polyaniline/graphite (PANI/G) composite in a fully-printed potentiometric pH sensor and the effect of graphite loading on sensor functionality. PANI/G composites in different ratios were aerosol-jet printed on Ag/AgCl with and without a graphite layer as the working electrode in a two-electrode potentiometric sensor on a flexible substrate. The role of graphite layer on working electrode in functionality of the sensor has been investigated. The PANI/G composites were prepared by a solution processing method using a graphite paste and polyaniline emeraldine salt powder. Samples were characterized by XRD, SEM, and FTIR analysis to investigate the relations between the physical and chemical relations and the performance of the sensors. The sensors were tested in the pH range from 3 to 10, exhibiting a linear, stable and near-Nernstian sensitivity of 53 mV pH −1 and a response time of 15 s.